The Effectiveness of The Scientific Approach to Improve Student Learning Outcomes - Firman, Firman; Baedhowi, Baedhowi; Murtini, Wiedy (International Journal of Active Learning, 2018)
The purpose of this research is to analyze the effectiveness of the scientific approach of Economics with modules that have been developed to improve the learning results of high school students. This research is the development of research based on the model of the Borg with Gall & i.e. stage introduction, development, and testing phase. The subject in this study is the SMA Negeri Mandailing Natal. Data collection techniques are used namely observation, interview, questionnaire, documentation, and test the results of the study. Data processing is carried out using SPSS. Operational field test using the design of one group pretest posttest design. Analysis of student learning test results in analysis using t-test test (independent samples test). The results showed that: the effectiveness of the economic lesson module with scientific approach showed that the average results of experimental classes after using the learning modules developed of 85.00 from earlier amounted to 65.00, and the control classes scored an average of 78.00 from previous 66.00. These values indicate that the developed modules can improve student learning result effectively.